Perception of IEQ factors on workplace satisfaction using Kano satisfaction model: a case study of malls in hot-humid climate - Idowu, Ibiyeye Aminat; Ja’afar, Mohd Fakri Zaky; Shari, Zalina; Dahlan, Nur Dalilah; Shamang, Kasham J. (Universiti Kebangsaan Malaysia Press, 2021)
This study reveals retailers’ perception of and their preference to some selected IEQ factors in relation to their workplace. Retailers of two types of malls (mixed-mode ventilated and Air conditioned malls) were studied under the following objectives: 1) To determine the retailers’ perception of some IEQ factors in each mall, and 2) To develop a pattern of the impact of retailers’ perception of some IEQ factors on their overall workplace satisfaction using the Kano satisfaction model. A subjective IEQ measurement was carried out and descriptive analysis was done on retailers’ responses to reveal their level of satisfaction after which a regression analysis was carried out on their perception of some IEQ factors. The results revealed that the air-conditioned ventilated mall recorded the highest mean satisfaction votes. Results also indicated that retailers in the mixed-mode ventilated malls considered air movement within their workplace as a necessity as the negative influence has a greater impact (regression coefficient 3.35*, -4.29*) on overall satisfaction. However, the absolute magnitude of the impact between satisfied and dissatisfied groups is not significantly different, thus, ‘air movement’ in the mixed-mode ventilated malls is categorized as proportional factor. Whereas, retailers in the AC mall responded to satisfactory air movement as something not expected (regression coefficient 3.27**, -2.19NS). On the other hand, retailers in the AC mall expected a controlled environment like theirs to thermally satisfy its occupants. Findings from this study will provide a better understanding of workers’ expectations and concerns with regard to their indoor environmental conditions.